Kinematic Collisionless Relaxation of Ions in Supercritical Shocks - Gedalin, Michael (Frontiers in Physics, 2019)
We show that kinematic collisionless relaxation in the macroscopic electric and magnetic fields plays the main role in the formation of the downstream ion distributions in a super-critical shock with ion reflection present. It is done by comparison of a theoretically predicted magnetic profile with the magnetic profile of a shocks observed by MMS mission. It is shown that pressure balance remains the main constraint for the shock stability.